Perilaku Seksual Remaja di Lingkungan Lokalisasi Kabupaten Sidoarjo - Mustalia, Mustalia; Suryoputro, Antono; Widjanarko, Bagoes (Jurnal Promosi Kesehatan Indonesia, 2016)
ABSTRACTSexual behavior as every conducts driven by sexual desire, either for other sex or even same sex. The purpose of this research to recognize Adolescent Sexual behavior in localization area of Sidoarjo regency. It is done a research due to still high adolescent sexual behavior happened in localization. This research as quantitave research with cross-sectional sampling with minimally sample size. This research performed in localization of Sidoarjo regency done by assessing adolescent in questionnaire sheet. Population of the research is teenager who lived at localization area of Sidoarjo regency as 221 respondents with sample of 140 respondets. Become inclusive criteria that is teenage who lived around localization area, age 12-18 years old, unmarried, not prostitute and ready to be respondent. Which become dependent variable and independent variable are sexual behavior. Data collected then processed by using chi square test indicating that p value > 0,05. Conclusion of this research show there is adolescent sexual behavior in localization area of Sidoarjo regency.Keywords: sexual behavior